PENGARUH KEBIJAKAN PERUSAHAAN TERHADAP SOLIDARITAS BURUH PADA MASA PANDEMI COVID-19 (STUDI DESKRIPTIF PADA BURUH PABRIK DI CIBODAS CAMPAKA) - Moch. Gilang Ramadhan, Gilang (2020)
The possible development of social issues such as the existence of current lagging communities, the industrial decline of society, the rise of criminal acts, and then forth is several threats from the existence of COVID-19 pandemic. Unfortunately, the policies that have stood so far could not be clear benefits. Departing from the issue raises labor dissatisfaction with policies that cannot satisfy the normative demands and social guarantee. Thus, the opinion of labor solidarity to fight for its rights and authority was born from that background. This research finds out the influence of corporate strategies on labor solidarity during the COVID-19 pandemic in many corporations in Cibodas Campaka. This research uses a quantitative approach with descriptive method, data collection technique using a closed questionnaire with the help of Google Forms spread through Instagram and WhatsApp. The results illustrated that (1) the level of influence of corporate policies during the COVID-19 pandemic is on the high levels, it means the regulation that made among health protocol and labor activity restriction who working in the factory that have an influence of themselves; (2) the level of labor solidarity in the COVID-19 pandemic was classified in average levels, that means that the sense of security of fellow workers is appropriately maintained; (3) The effect of the company's policy on labor solidarity during the COVID-19 pandemic in Cibodas Campaka has a positive and a powerful level of relationship. Policy becomes an important factor in fulfilling the welfare of workers, because it creates labor solidarity based on the unfulfilled normative demands and social guarantee. The implication of this research is that both governments and companies can ever consider any policy making that will be created.